The Role of Cynicism in Social Responses to the Climate Emergency - Debra J. Davidson (Socius)
Cynicism poses a potentially formidable barrier to personal and collective investments in addressing the climate emergency that has yet to receive substantive research attention. In this article, the results of a qualitative study involving interviews with 74 participants in Canada and the United States regarding personal perspectives on climate change are presented. Several different forms of cynicism were expressed across the sample, including media cynicism, government cynicism, policy cynicism, political economy cynicism, human nature cynicism, and science cynicism. Using cooccurrence analysis, cynicism was found to be strongly associated with confidence in societal response to the climate emergency, and personal feelings of powerlessness. Although not the most prevalent cynicism code, political economy cynicism had the strongest level of cooccurrence with low response confidence and powerlessness. The implications for research and praxis are discussed.